Perception towards Firm Value in Nepalese Banking Sector - Gautam, Madhusudan (Management Dynamics, 2021)
Determining firm value in commercial banks is challenging because its value is affected by various internal and external determinants. Using a structured questionnaire, this study aims to assess a survey on the perception of firm value in Nepalese commercial banks. Three hundred questionnaires were distributed equally among depositors and investors. Among them, 183 questionnaires were collected into usable form. The findings revealed that depositors and investors perceive that deposit, profitability, capital adequacy and good governance affect bank value. Publication of financial reports is one of the major influencing factors of bank value. Credit risk has a negative effect on firm value in banks. Finally, the study concludes that firm value primarily depends on managerial efficiency followed by market information, strong liquidity position, credit risk, earnings position, use of the loan, leverage and size, respectively, in Nepalese commercial banks.